Effects of Body Position on Respiratory Pressure and Muscle Activity in Amyotrophic Lateral Sclerosis and Healthy Subjects. - Maciel, Ana Cristina de Medeiros Garcia; da Silva, Ana Aline Marcelino; Medeiros da Fonseca, Jéssica Danielle; Vieira, Rayane Grayce da Silva; da Silva, Lailane Saturnino; Lima, Thiago Bezerra Wanderley e; Pondofe, Karen de Medeiros; Otto-Yáñez, Matías; Torres-Castro, Rodrigo; Vera-Uribe, Roberto; Vilaró, Jordi; Dourado Junior, Mario Emilio Teixeira; et al. (Respiratory Care, 2026)
Background: Amyotrophic lateral sclerosis (ALS) is a fatal heterogeneous neurodegenerative disease characterized by the degeneration of both upper and lower motor neurons and spinal cord. Measurement of respiratory muscle strength has been shown to be an important assessment in the decision-making process and can be assessed by maximum inspiratory (PImax) and expiratory pressures (PEmax), sniff nasal inspiratory (SNIP) and expiratory (SNEP) pressures. Body position appears to have a significant effect on respiratory muscle strength. The aim of this study was to observe the difference in peak values of SNIP and SNEP of the respiratory muscles measured in 2 different positions (seated and supine with 45° elevation) in subjects with ALS and a group of matched healthy subjects. Methods: This is a case–control study of subjects with ALS and healthy subjects. Spirometry and surface electromyography (EMG) of the sternocleidomastoid, scalene, rectus abdominis, and external oblique muscles were assessed during PImax and PEmax maneuvers in the seated position, and SNIP and SNEP in the seated and supine positions at 45° elevation (randomized). Results: SNEP values in the 45° elevation were lower than in the sitting position in ALS (70.3 ± 26.7 vs 57.3 ± 22.8 cm H2O, P =.041). SNIP and SNEP were lower in ALS in the 45° elevation compared with healthy subjects (69.1 ± 27.2 vs 95.5 ± 23.5 cm H2O; 57.3 ± 22.5 vs 92.7 ± 26.4 cm H2O, P =.041). In subjects with ALS, baseline electromyographic activity of the sternocleidomastoid muscle at rest was higher than in healthy subjects in both positions (P =.041). No significant differences in electrical activity were found for other variables and measurements. Conclusions: In ALS, nasal pressure may be affected by reduced diaphragm and abdominal muscle effectiveness in the supine position. The sternocleidomastoid muscle showed increased electrical activity in the supine position with 45° elevation compared with controls, which may indicate muscle weakness.